Raudhatul Athfal Teachers’ Preferences for Digital Presentation Media to Optimize Classroom Learning - Ardhina Asri; Husin; Huda; Yusria (JTP - Jurnal Teknologi Pendidikan, 2026)
Raudhatul Athfal (RA) institutions in Jambi Province face a critical infrastructure paradox in implementing the digital transformation mandated by the Merdeka Curriculum: while 100% of schools provide teachers with computers/laptops and reliable internet, only 50% are equipped with projectors or LCDs, a 50-percentage-point gap that constrains the delivery of digital presentations. This study aimed to (1) characterize the accessibility of digital resources and usage patterns of PowerPoint and Canva, (2) examine teachers’ perceptions of the features, usability, and impact of both media, and (3) determine training needs and facility-acquisition recommendations. Twenty RA teachers from three districts/cities in Jambi Province (Tanjung Jabung Barat, Kota Jambi, and Muaro Jambi) were purposively sampled for this descriptive quantitative study; data were gathered through a validated 16-item Google Forms questionnaire and analyzed using descriptive statistics, response categorization, and thematic coding. Teachers viewed digital media as improving teaching quality (100%) and student engagement (95%), with Canva preferred over PowerPoint by 90% of respondents for its user-friendliness and Islamic-appropriate templates. Only 60% received institutional technical support despite universal (100%) demand for government-funded training, indicating that multi-level intervention is required to close Jambi’s RA infrastructure and digital-competency gap.